CALCULATING INTRINSIC VALUE OF STOCK: SUU JOINT STOCK COMPANY - Odbileg.D; Budmaa.Ts; Delgerbayar.E; Davaadorj.B; Erdenechuluun.J; Munkh-Erdene.A (Journal of Business and Innovation (Бизнес & Инноваци), 2023)
In order to develop our nation’s financial market, it is crucial to improve the securities market indicators. In recent years, people’s knowledge of securities has been broadened and government has supported the market by legal policy. As result, the Mongolian Stock Exchange TOP-20 index has increased by 25 percent in the first quarter of 2018. Investor’s decision and company’s intrinsic value of stock are key moving impetus to stock market’s development.